2003
DOI: 10.1095/biolreprod.102.006494
|View full text |Cite
|
Sign up to set email alerts
|

Development of Parthenogenetic Rat Embryos1

Abstract: In an effort to establish cloning technology for the rat, we tested several methods (electric stimulation, treatment with ethanol or strontium) for the parthenogenetic activation of rat oocytes. We observed marked individual differences among rats of the outbred Wistar strain in their ability to yield activatable oocytes. These differences were independent of the activation protocol and may be due to a genetic predisposition that is crucial for the parthenogenetic activation of oocytes. The activation of oocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
36
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 48 publications
4
36
0
Order By: Relevance
“…Second polar body extrusion and fragmented cytoplasm increased as CM exposure exceeded the optimum time. A small fraction (6%) of mouse MII oocytes cultured in DMEM-HG or CZB without any known parthenogenetic stimulants initiated parthenogenetic activation spontaneously, which is a common phenomenon in lower vertebrate species and amphibians (28).…”
Section: Discussionmentioning
confidence: 99%
“…Second polar body extrusion and fragmented cytoplasm increased as CM exposure exceeded the optimum time. A small fraction (6%) of mouse MII oocytes cultured in DMEM-HG or CZB without any known parthenogenetic stimulants initiated parthenogenetic activation spontaneously, which is a common phenomenon in lower vertebrate species and amphibians (28).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it is well documented in several mammalian species that complete activation and pronuclear formation is dependent upon the age of the oocyte with regard to ovulation. In general, while aged oocytes are easily activated even with artificial stimuli inducing a single Ca 2þ rise, recently ovulated oocytes often arrest at MIII and repetitive Ca 2þ transients or combined treatments with protein synthesis or phosphorylation inhibitors are required for the completion of meiosis and entry into interphase in these young oocytes (Collas et al 1989, Kubiak et al 1993, Presicce & Yang 1994, Swann & Ozil 1994, Krivokharchenko et al 2003. Although it is beyond the scope of the present study, further analysis of oocyte maturation kinetics after hCG injection, quantification of IP 3 R levels and measurement of the Ca 2þ transients induced by ethanol and strontium in oocytes from the four strains of mice could be performed to assess this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…Information on the effect of oocyte age on the response to activation treatment in the rat is very limited. A study in Wistar rats [8] showed that the use of ethanol for parthenogenetic activation was highly effective only for aged oocytes (22-2 4 h after hCG). However, the efficiencies of activation and cleavage rate were equal for all ages of oocytes when they were treated with strontium [8].…”
Section: Discussionmentioning
confidence: 99%
“…Since activation of the recipient oocyte is a crucial step in successful nuc lear transfer techniques [8 ], inco mplete activation of reconstructed embryos may in part be responsible for the difficulty of rat nuclear transfer. At present, the available information regarding parthenogenetic activation of rat oocytes is limited.…”
mentioning
confidence: 99%
See 1 more Smart Citation